Microstructure and microwave dielectric properties of Al2O3 added Li2ZnTi3O8 ceramics. Issue 8 (1st June 2018) - Ren, Junqing; Bi, Ke; Fu, Xiuli; Peng, Zhijian
Abstract: Recently, the rapid development of advanced communication systems increasingly strongly demands high-performance microwave dielectric ceramics in microwave circuits. Among them, Li2 ZnTi3 O8 ceramics have been one of the most widely investigated species, due to its high quality factor, moderate firing conditions and low cost. However, the dielectric constants of the already reported Li2 ZnTi3 O8 ceramics are fixed in a narrow range, limiting their wider applications. To adjust the dielectric constant of the Li2 ZnTi3 O8 based ceramics, in this work Li2 ZnTi3 O8 ceramics added with different amounts of Al2 O3 (0–8 wt%) were prepared by conventional solid-state reaction. The microstructure and microwave dielectric properties of the samples were investigated. Due to the addition of Al2 O3, the sintering temperature of the ceramics would be increased somewhat. Some Al 3+ ions could substitute for Ti 4+ ions in Li2 ZnTi3 O8, and the added Al2 O3 would react with ZnO to produce a ZnAl2 O4 phase accompanying with the formation of TiO2 phase, which would inhibit the growth of Li2 ZnTi3 O8 grains. The dielectric constant of the finally obtained ceramics would be reduced from 26.2 to 17.9, although the quality factors of the obtained ceramics would decrease somewhat and the temperature coefficient of resonant frequency would deviate further from zero.